The Suzuki Cross-Coupling Reaction of l-Ascorbic Acid: C2-Arylation and Evaluation as Antiproliferative Agents - Kote, Santosh R.; Dhage, Ganesh R.; Thopate, Shankar R.; Mishra, Ratnakar; Khan, Ayesha A. (Synthesis, 2015)
The C2-arylation of l-ascorbic acid, via the Suzuki cross-coupling reaction of 3-O-alkyl-5,6-O-isopropylidene-2-O-triflyl-l-ascorbic acid with boronic acids, was investigated. Various arylboronic acids were efficiently coupled under the present protocol. The biological screening results revealed that these compounds were selective anticancer agents. The most potent compound (R)-5-[(S)-2,2-dimethyl-1,3-dioxolan-4-yl]-3-(furan-2-yl)-4-methoxyfuran-2(5H)-one exhibits IC50 values of 6.7, 6.4, and 5.8 μM against human cervical cell line (HeLa), breast cancer cell line (MCF-7), and leukemic cell line (HL-60), respectively.
Keywords: antitumor agents; arylation; cross-coupling; lactones; vitamins